Using Documentary Films in Developing Student’s Critical Thinking Skill: Senior High School Context - Jumiati Lanta; Suleha Ecca; Asyanti Asyanti; M.Hijaz Tahir (Utamax : Journal of Ultimate Research and Trends in Education, 2019)
The quantitative study is aimed to know whether documentary films can be applied to foster students' critical thinking skills. This research was conducted in Class X SMA Negeri 10 Sidenreng Rappang, with a total population of 72 students. Samples were drawn from the entire population by taking 2 classes, namely X IPA as an experimental group of 26 students and X IPS as a control group of 25 students. Data were collected through a critical thinking ability test instrument based on critical thinking indicators, then processed with data analysis using the Mean score (average) and SPSS 2.0. Results of the study showed that the experimental group, which were taught to use the documentary, obtain average value is higher compared with the controls group in fostering the ability to think critically, especially on the subjects of Indonesian with developing materials with the opinion of exposition text. Average score results in critical thinking skills with a documentary film is 91.76 with the results of a significant test of the test independent of 10.878 while the average score of the results that are taught without using documentary 70.84 with value significant 2.009. Based on the results of data analysis, this present study ascertained that documentary films could foster students' critical thinking skills.